2020
DOI: 10.1017/jlg.2020.9
|View full text |Cite
|
Sign up to set email alerts
|

Production and perception of the Pin-Penmerger

Abstract: This study presents the first US-wide survey of the pin-pen merger since Labov, Ash & Boberg (2006). Production and perception data were collected from 277 speakers from across the country, with perception-only data from an additional 94 speakers; these data largely replicated previous findings about the social and geographic distribution of the merger. An examination of production and perception data together showed that near merger—in which speakers cannot hear the difference between pin and pen words, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Similarly, associations can be observed between race and dialects/ethnolects of English. For example, in the United States, PIN/PEN mergers occur more among African American speakers than White speakers, even in geographic areas where PIN/PEN mergers are more common (Austen, 2020; Labov, 2006). Together, the work from the past two paragraphs highlights the importance of real-world experience on forming sociolinguistic associations, as well as how these associations may influence our future listening experiences.…”
Section: Sociolinguistic Learningmentioning
confidence: 99%
“…Similarly, associations can be observed between race and dialects/ethnolects of English. For example, in the United States, PIN/PEN mergers occur more among African American speakers than White speakers, even in geographic areas where PIN/PEN mergers are more common (Austen, 2020; Labov, 2006). Together, the work from the past two paragraphs highlights the importance of real-world experience on forming sociolinguistic associations, as well as how these associations may influence our future listening experiences.…”
Section: Sociolinguistic Learningmentioning
confidence: 99%
“…Practically speaking, however, this method is known to be difficult to calibrate. For instance, several researchers have run into the issue of how to interpret results of participants who perform well above chance in accurately discriminating between words containing non-native regional contrasts (e.g., Austen 2020;Bowie 2000;Labov et al 1991;Thomas and Hay 2005). This has led on occasion to listeners who do not show 100% accuracy in distinguishing minimal pairs to be considered for analytic purposes as perceptually merged.…”
Section: Cross-dialectal Perception Of Mergersmentioning
confidence: 99%
“…Baranowski (2013), examining the pin-pen [I-ε] merger in Charleston, South Carolina, found that speakers were more likely to be merged in production than perception, although there was no significant difference between production and perception for cot-caught. Austen (2020), tracking the distribution of the pin-pen [I-ε] merger across the United States, found that almost all speakers who merged the two phones were still able to discriminate them above chance (but below 100% accuracy) in a two-alternative forced choice identification task. For the Ellen-Allen merger in New Zealand (Thomas and Hay, 2005;Hay et al, 2013), and for the cot-caught merger in Hawai'i and the western United States (Hay et al, 2013), speakers who were merged in production could still discriminate between both pairs in perception.…”
Section: Sound Change Trajectoriesmentioning
confidence: 99%